Tangential cranial ballistic impact: An illustration of the limitations of post-mortem CT scan?. (May 2018) - Delteil, Clémence; Gach, Pierre; Ben Nejma, Noura; Capasso, Françoise; Perich, Pierre; Massiani, Pierre; Gorincour, Guillaume; Piercecchi-Marti, Marie-Dominique; Tuchtan, Lucille
Highlights: Post-mortem imaging has become more frequently used in ballistic context. The interpretation of computed tomography (CT) can be a very complex matter after quasi-tangential cranial ballistic impact. CT findings must be interpreted in close comparison with autopsy findings. Abstract: Post-mortem imaging has become more frequently used in forensic procedures, notably in a ballistic context. Despite many advances in this field, the interpretation of computed tomography (CT) can be a very complex matter. Our case illustrates the difficulties of interpretation after quasi-tangential cranial ballistic impact and keyhole wounds. These wounds are difficult to visualize on CT and are among the factors complicating the precise determination of ballistics. These sources of error remind us that CT findings must be interpreted in close comparison with autopsy findings.